Effect of Angle of Attack on Airfoil NACA 0012 Performance - Ali Akbar (Universitas Muhammadiyah Sidoarjo, 2020)
Airfoil is an aerodynamic form intended to produce a lift force with the smallest drag force. When an airfoil is passed through a fluid flow that causes interaction between the air flow and the surface, variations in velocity and pressure will occur along the top and bottom surfaces of the airfoil, as well as the front and back of the airfoil. The difference in pressure between the upper and lower surface of the airfoil is what causes the resultant force in the direction perpendicular to the direction of fluid flow, this force is called the lift force (lift). In this experiment NACA 0012 airfoil experiments have been carried out using simple wind tunnel. Experiments were conducted with the aim to determine the effect of the angle of attack on the performance of the NACA 0012 airfoil which then analyzed the lift force of the NACA 0012 airfoil. The variation of the angle of attack used was 0 °, 3 °, 6 °, 9 °, 12 °, and 15 ° and used wind speed of 21.5 m / s. The greatest lift force is obtained at an angle of attack of 9 ° with a value of 0.981 while the largest lifting coefficient with a value of 0.106. The greater the angle of attack the greater the airfoil lift force, but for symmetrical airfoil stall at an angle that is too large